Effects of mineral trioxide aggregate, calcium hydroxide, biodentine and Emdogain on osteogenesis, Odontogenesis, angiogenesis and cell viability of dental pulp stem cells - Abdel-Rahman Youssef; Ramy Emara; Mohiuddin M. Taher; Faisal A. Al-Allaf; Majed Almalki; Mazen A. Almasri; Shahid S. Siddiqui (BMC, 2019)
Abstract Background Vital pulp therapy preserves and maintains the integrity and the health of dental pulp tissue that has been injured by trauma, caries or restorative procedures. The enhancement of cells viability and formation of reparative dentine and new blood vessels are vital determinants of the success of direct pulp capping. Therefore, the aims of this study was to evaluate and compare the in vitro osteogenic, odontogenic and angiogenic effects of mineral trioxide aggregate (MTA), calcium hydroxide [Ca(OH)2], Biodentine and Emdogain on dental pulp stem cells (DPSCs) and examine the effects of the tested materials on cell viability. Methods DPSCs were treated with MTA, Ca(OH)2, Biodentine or Emdogain. Untreated cells were used as control. The cell viability was measured by MTT assay on day 3. Real-Time PCR with SYBR green was used to quantify the gene expression levels of osteogenic markers (alkaline phosphatase and osteopontin), odontogenic marker (dentin sialophosphoprotein) and angiogenic factor (vascular endothelial growth factor) on day 7 and day 14. Results All capping materials showed variable cytotoxicity against DPSCs (77% for Emdogain, 53% for MTA, 26% for Biodentine and 16% for Ca(OH)2 compared to control (P value < 0.0001). Osteopontin (OPN) and dentin sialophosphoprotein (DSPP) gene expression was increased by all four materials. However, alkaline phosphatase (ALP) was upregulated by all materials except Emdogain. Vascular endothelial growth factor (VEGF) expression was upregulated by all four tested materials except Ca(OH)2. Conclusions Our results suggest MTA, Biodentine and Emdogain exhibit similar attributes and may score better than Ca(OH)2. Emdogain could be a promising alternative to MTA and Biodentine in enhancing pulp repair capacity following dental pulp injury. However, further future research is required to assess the clinical outcomes and compare it with the in vitro findings.